Pengaruh Belanja Modal dan Belanja Pegawai Terhadap Pertumbuhan Ekonomi Daerah di Kawasan Barat Indonesia - Nurul Fitri; Sasqia Putri (Jurnal EMT KITA, 2019)
This study aims to analyze the effect of capital expenditure and personnel expenditure on regional economic growth in western Indonesia. The data used is a panel data of 10 provinces during the period 2008-2015. The econometric models used to analyze the functional relationship of these variables consisted of the fixed effect method of panel regression, and the Granger causality test. The study found that capital expenditure has a positive but not significant effect on regional economic growth. Conversely, personnel expenditure has a positive and significant effect. Granger causality test results indicate a one-way causality from personnel expenditure and capital expenditure to economic growth and from personnel expenditure to capital expenditure.